What Is HIPAA and How Does It Apply to AI in Healthcare? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2015)
The healthcare industry is undergoing a significant transformation, driven by the rapid advancements in Artificial Intelligence (AI). From diagnostic tools t...
Keywords: Healthcare Data Privacy and Security; HIPAA; Apply; Healthcare; Artificial Intelligence; Machine Learning; Patient Care